Metabolic and molecular insights on limonin biotransformation by Pseudomonas putida - Malik, Meenakshi (My University, 2012)
Microbial whole cells and their enzymes are implicated as potential biocatalysts in several biotechnological processes. However suitable biocatalysts for removal of bitter triterpenoids in citrus juices are currently lacking and requires due consideration. Limonin, a triterpenoid is generated in freshly squeezed citrus juices and imparts bitterness making it unacceptable to consumers thereby impeding industrial processing of citrus juices. In this study, the unique metabolic feature of Pseudomonas putida G7 to biotransform polycyclic aromatic compounds was exploited based on its ability to utilize limonin as a sole carbon and energy source. First, an attempt was made to elucidate the limonin catabolic abilities, enzyme(s) and gene(s) in P. putida G7. Then, these results were used to formulate a process for limonin biotransformation, viable under real time conditions in citrus juice. Physiological studies revealed that P. puitda G7 could biotransform limonin in synthetic minimal medium by 64% at an alkaline pH 8, 37°C, in 36h. The molecular characterization of limonin biotransformation revealed the association of glutamate symporter in limonin utilization and established the role of an indigenous 83 kb NAH plasmid for limonin bioconversion in P. putida G7. The biochemical insights suggested the potential involvement of a periplasmic isofunctional dehydrogenase in biotransformation of limonin. A 26 fold purification of the periplasmic dehydrogenase was achieved, the purified enzyme was a monomer of 26 kDa and converted limonin by 76% to non bitter defuran limonin upon incubation at pH 8 for 150 min at 30°C. The Michaelis constant (KM) measured for limonin was 4.5µM and Vmax was 8µmoles/min. However both whole cells as well as application of pure enzyme for limonin biotransformation in citrus juices were not practicable, therefore improvements in whole cells was sought. Substantial enhancement in limonin biotransformation was achieved by using alginate immobilized whole cells and conferred reusability of P. putida cells. Lower bioconversion rates observed during subsequent batch cycles was possibly due to diffusional restriction of substrate or products across the cellular membrane. Permeabilization of P. putida with EDTA (1 µg/ml) for 15 min alleviated diffusional restriction and enhanced limonin bioconversion to 73% within 180 min. Entrapment of permeabilized P. putida cells in dialysis membrane prior to application further enhanced the biotransformation rate to 76.7% presumably by affording mechanical stability to permeabilized cells. The residual limonin level in the treated citrus juice obtained using permeabilized cells, remained far below the threshold limit of human detection and retained its inherent antioxidative properties assuring consumer acceptance. The viability of dialysis membrane based bioreactor developed by employing the permeabilized P. putida G7 promises an important industrial strategy in reducing limonin levels in mandarin juices.
Doctor of Philosophy
Keywords: Limonin biotransformation; pseuomonas putida; mandarine juice; limonin dehydrogenase; glutamate transporter